The Gambia Education Sector Public Expenditure Review : An Efficiency, Effectiveness, Equity, Adequacy, and Sustainability Analysis - World Bank Group (World Bank, Washington, DC, 2017)
The structure of this report is organized into 10 sections. Following the Introduction, section two discusses the country context in terms of demographic trends and potential dividends and the fiscal space in relation to the increasing social sector demand. Section three provides an overview of the education sector context and structure, together with a chronological order of the education sector’s policies, goals, and priorities. Section four analyzes key education sector performance indicators. Section five analyzes the education sector financing such as the budget framework and budget process, main actors, sources of funding, trends in public expenditure, and budget allocation. Section six assesses the adequacy and sustainability of public spending. Section seven examines education sector management issues focusing on the efficiency and effectiveness of resources utilization. Section eight examines equity, affordability, and the role of the government in protecting equity. Section nine simulates enrollment growth and the associated human and financial needs and provides projections of the labor force by educational attainment under various scenarios. The analysis is followed by section ten, a summary of the main findings and policy recommendations. The annex is divided into four sections: a methodological note, supporting tables, figures, and a section on examples of evaluated interventions.